Intravitreal Delivery of Melatonin Is Protective Against the Photoreceptor Loss in Mice: A Potential Therapeutic Strategy for Degenerative Retinopathy - Li, Chong; Tian, Yi; Yao, Anhui; Zha, Xiaobing; Zhang, Jianbin; Tao, Ye (Frontiers in Pharmacology, 2020)
Melatonin is a circadian hormone with potent cytoprotective effects. Retinitis pigmentosa (RP) comprises a heterogeneous group of inherent retinopathies that characterized by the photoreceptor death in bilateral eyes. The N-methyl-N-nitrosourea (MNU) administered mouse is a type of chemically induced RP model with rapid progressive rate. We intend to study the melatonin mediated effects on the MNU administered mice. Melatonin was delivered into the vitreous body of the MNU administered mice. Subsequently, the melatonin treated mice were subjected to histological analysis, optokinetic behavior tests, spectral-domain optical coherence tomography(SD-OCT), and electroretinogram(ERG) examination. Multi-electrodes array (MEA) was used to analyze the status of visual signal transmission within retinal circuits. Biochemical analysis was performed to quantify the expression levels of antioxidative enzymes, oxidative stress markers, and apoptotic factors in the retinas. The intravitreal injection of melatonin ameliorated effectively the MNU induced photoreceptor degeneration. Melatonin therapy mitigated the spontaneous firing response, and preserved the basic configurations of visual signal pathway in MNU administered mice. MEA is effective to evaluate the pharmacological effects on retina. Of note, the cone photoreceptors in degenerative retinas were rescued efficiently by melatonin therapy. Melatonin afforded these protective effects by modulating the apoptotic cascades and alleviating the oxidative stress. These findings suggest that melatonin could act as an alternative treatment for degenerative retinopathy. Melatonin might be used in combination with other therapeutic approaches to alleviate the photoreceptor loss and preserve the visual function of RP patients.